(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
This research consist in conducting a theoretical approach to an economic model based on the similarities of Western economies (capitalism) and Islam, which was effected by developing dimensioning of both cultures, with the intention of contrasting economic, from an economic perspective, to highlight the strengths of the two economies, this analysis constitute the basic inputs for the proposed principles. The research was framed within the social sciences and addressed through a quality-quantitative model. The study was of analytical-descriptive, documentary and bibliographic database. The achievement of the objectives was achieved methodologically through methodology based contrast normative comparison. In terms of design will consist of two (02) stages, the first stage contrast economic Islamic principles and capitalist principles, resulting in the foundations, which serve as the basis of the approach of a theoretical economic model for countries whether they are capitalists or Islamic, will enable a new economic man-centered perspective